The Role Of Additional Employee Income In Moderating The Effect Of Work Discipline, Charismatic Leadership, And Non-Physical Work Environment On Work Productivity - Rudi Hermantoni; Mulyadi Mulyadi; Ahmad Basri (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to examine the effect of work discipline, charismatic leadership, and non-physical work environment on work productivity, as well as the moderating role of additional employee income. The research population included 60 employees of the Regional Secretariat of Musi Rawas Regency with a saturated sampling technique. Data analysis was conducted using linear regression, t-test, and Moderated Regression Analysis (MRA). The results show that work discipline and charismatic leadership have a significant effect on productivity. The impact of both is more substantial when moderated by income incentives. Therefore, the importance of additional performance-based employee income. The non-physical work environment also had a positive impact but was not moderated by additional employee income. This indicates the dominance of intrinsic social and psychological factors. In addition, additional employee income can directly increase productivity through healthy competition between employees. The limitations of the study lie in the narrow scope of the institution and the limited number of respondents. The contribution of this study lies in the integration of behavioral, leadership, environmental, and additional employee income approaches in improving productivity. The novelty of the study appears in the analysis of the moderating role of additional employee income in the relationship between public sector organizational variables.